Estrogen receptor β/substance P signaling in spinal cord mediates antinociceptive effect in a mouse model of discogenic low back pain - Song, Xiao-Xing; Jin, Lin-Yu; Li, Qiang; Li, Xin-Feng; Luo, Yan (Frontiers in Cellular Neuroscience, 2023)
Discogenic low back pain (DLBP) is the most commonly described form of back pain. Our previous studies indicated that estrogen-dependent DLBP mechanism was mediated by estrogen receptors (ERs) in the intervertebral disc (IVD) tissue, and the IVD degeneration degree is accompanied by downregulation of ERs, particularly ERβ. However, the neuropathological mechanisms underlying ERs modulation of DLBP are still not well understood. In this study, we investigated the antinociceptive effects of selective ERβ agonists on DLBP-related behavior by regulating substance P in spinal cord and dorsal root ganglia. Two weeks after ovariectomies, eighteen-week-old female mice were randomly separated into four groups: control group; DLBP sham surgery plus vehicle group; DLBP plus vehicle group; DLBP plus ERβ-specific agonist diarylpropionitrile (DPN) group. Behavioral data was collected including behavioral measures of axial back pain (grip force and tail suspension tests) and radiating hypersensitivity (mechanical sensitivity and cold sensitivity test). Dual label scanning confocal immunofluorescence microscopy was used to observe spatial colocalization of ERβ and substance P in spinal cord. Substance P changes in spinal cord and dorsal root ganglia were measured by immunohistochemistry and real-time PCR. ERβ activation could improve both axial and radiating behavioral disorders of DLBP. DPN facilitated the decrease of the amount of time in immobility one week after agonist administration. And at the time point of three weeks, DPN group spent significantly less time in immobility than the vehicle group. In the grip strength tests, starting from postoperative week 1 to week 3, DPN injection DLBP mice showed more resistance to stretch than the vehicle injection DLBP mice. Significant differences of cold withdrawal latency time were observed between the DLBP plus DPN injection and DLBP vehicle injection groups at 2- and 3-week injection time point. DPN significantly reversed the paw withdrawal threshold of DLBP mice at the time point of one, two and three weeks. Substance P colocalized with ERβ in spinal dorsal horn, mainly in laminae I and II, a connection site of pain transmission.